Peluang dan Tantangan Pariwisata Kuliner: Studi Kasus Desa Pujon Kidul Malang Jawa Timur - Ardiyansah, Ardiyansah (FIA Unkris Press, 2025)
Culinary tourism has become an important strategy in the development of community-based tourism villages, as it integrates local economic, social, and cultural potentials. Pujon Kidul Village in Malang Regency, East Java, represents a tourism village that has successfully positioned culinary tourism as a core element of rural tourism experiences. This study aims to analyze the opportunities and challenges of culinary tourism development in Pujon Kidul Village and its implications for sustainable rural development. A qualitative approach with a case study design was employed in this research. Data were collected through in-depth interviews, field observations, and document analysis involving tourism village managers, culinary business actors, village officials, and local residents. The data were analyzed using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that culinary tourism opportunities in Pujon Kidul Village are supported by the availability of local raw materials, strong community participation, village institutional support, and the appeal of rural-based culinary experiences. However, several challenges were also identified, including limited human resource capacity, inconsistent product quality standards, environmental pressures, and competition among tourism destinations. This study highlights that the success of culinary tourism development depends on balanced management between economic opportunities and sustainability challenges. The findings are expected to contribute to academic discussions and serve as a reference for policymakers in developing sustainable, community-based culinary tourism.